Subcellular dynamics of variants of SG2NA in NIH3T3 fibroblasts. (4th December 2019) - Chauhan, Pooja; Gupta, Richa; Jain, Buddhi P.; Pandey, Shweta; Goswami, Shyamal K.
Abstract: SG2NA, a WD40 repeat protein of the Striatin subfamily, has four splicing and one messenger RNA edit variants. It is fast emerging as a scaffold for multimeric signaling complexes with roles in tissue development and disease. The green fluorescent protein (GFP)‐tagged variants of SG2NA were ectopically expressed in NIH3T3 cells and their modulation by serum and GSK3β‐ERK signaling were monitored. The 87, 78, and 35 kDa variants showed a biphasic modulation by serum till 24 h but the 52 kDa variant remained largely unresponsive. Inhibition of phosphatases by okadaic acid increased the levels of the endogenous 78 kDa and the ectopically expressed GFP‐tagged 87 and 78 kDa SG2NAs. Contrastingly, okadaic acid treatment reduced the level of GFP‐tagged 35 kDa SG2NA, suggesting differential modes of their stability through phosphorylation‐dephosphorylation. The inhibition of GSK3β by LiCl showed a gradual decrease in the levels of 78 kDa. In the case of the other variants viz, GFP‐tagged 35, 52, and 87 kDa, inhibition of GSK3β caused an initial increase followed by a decrease with a subtle difference in kinetics and intensities. Similar results were also seen upon inhibition of GSK3β by small interfering RNA. All the variants showed an increase followed by a decrease upon inhibition of extracellular‐signal‐regulated‐kinase (ERK). These variants are localized in the plasma membrane, endoplasmic reticulum, mitochondria, and the nucleus with different propensities and no discernable subcellular distribution was seen upon stimulation by serum and the inhibition of phosphatases, GSK3β, and ERK. Taken together, the variants of SG2NA are modulated by the kinase‐phosphatase network in a similar but characteristic manner. Abstract : Subcellular distribution of SG2NA variants. Different isoforms are marked by shape and colour and their relative position in the organelle are shown. In all locations, the level of the isoforms are modulated by phosphorylation and dephosphorylation as shown in rectangular blocks.